Overview of the powder metallurgy process - Hrairi, Meftah; Hussin, Asmu'i; Mohamad Ravi, Fadzly (IIUM Press, 2011)
Powder Metallurgy (P/M) is on the leading edge of new manufacturing processes for improved product quality and productivity. It is a cost-effective method of forming precision net-shape metal components that allows for more efficiently designed consumer and industrial products. The PIM industry continues to invest heavily in new technology to improve the properties of PIM products. One of the major goals for the conventional PIM industry is to increase the density to match the properties of wrought materials. New materials containing chromium, silicon and other non-conventional alloy systems were developed for higher performance. New lubricant systems are being developed for higher densities and enhanced properties, closing the gap with wrought materials